Authority Fragmentation in Blue Economy Governance in Coastal Singkawang: Fragmentasi Kewenangan dalam Tata Kelola Blue Economy di Pesisir Singkawang - Qurnia Indah Permata Sari; Taufik Akbar; Fathul Bari; Selamet Daroini (Universitas Indo Global Mandiri, 2026)
Purpose: This study analyzes governance challenges in blue economy implementation in coastal Singkawang by examining authority fragmentation, inter-actor coordination, and coastal community livelihoods. Design: This research uses a qualitative case study approach. Data were collected through in-depth interviews, field observations, and document analysis. The informants included representatives of municipal government agencies, provincial government agencies, fisher organizations, fishers, fish traders, and seafood processing actors. The data were analyzed thematically to identify patterns of authority distribution, inter-agency coordination, policy implementation, environmental management, conservation, and fisher livelihoods. Findings: The findings show that blue economy implementation in Singkawang is shaped by multi-level and cross-sectoral governance. Although authority over marine areas lies with the provincial and central governments, the municipal government continues to play a strategic role as the closest actor to coastal communities through fisher guidance, administrative facilitation, fuel recommendation services, seafood processing support, fish market governance, and coastal environmental management. Inter-agency coordination has developed through marine waste management, fishery product diversification training, and fisher group assistance, but institutional strengthening is still needed to ensure more consistent and sustainable implementation. Practical Implication: The findings highlight the need to strengthen coordination among municipal, provincial, and central governments, particularly in fisher services, seafood value-added activities, marine waste management, and mangrove-based coastal conservation. Originality/value: This study contributes to blue economy governance literature by showing that implementation in a non-metropolitan coastal city is shaped not only by marine resource potential, but also by authority fragmentation, coordination capacity, and the municipal government’s bridging role.